b b - Pius Weraman; Wawan Kurniawan; Devin Mahendika; Sri Handajani; Ernawati Umar (Postgraduate, University of Mataram, 2023)
The correlation between the satisfaction experienced by patients with the quality of nutritional services and the cleanliness of health clinics has an influence on the image of the hospital. This has implications for improving the quality of hospitals in providing food services and the cleanliness of health clinics by serving food that suits the needs of patients. This research was conducted with the aim of knowing patient satisfaction in service, food quality and cleanliness of health clinics. The research method used was a quantitative method with a cross sectional study design where the data sample was 53 people. Sampling was taken by total sampling method where the data will be analyzed using the paired t-test. The results of this research show that there is patient satisfaction with food quality of 75.5% with a p value of 0.064. Practically there is no difference between expectations and reality in this service. The patient satisfaction with the cleanliness of the health clinic was 75.5% at a p value of 0.083, which indicates there is no difference between expectations and reality. Apart from that, satisfaction with the appearance of food was 98.1% with a p value of 0.322. Then the satisfaction of the patients with the taste had a value of 83% with a p value of 0.064. Then the patient's satisfaction with the texture was 94.3% with a p value of 0.083. Then there is a sense of satisfaction with the time the food is served with a value of around 98.1% at a p value of 0.322.